Joining of continuous fiber reinforced thermoplastic/steel hybrid parts via undercutting pin structures and infrared heating - Julian Popp; Dietmar Drummer (Journal of Advanced Joining Processes, 2022)
Continuous fiber reinforced thermoplastics (CFRT)/steel hybrid parts offer promising properties and possibilities, which can exceed the capabilities of both individual materials. In this case, the joining operation presents the main challenge. This paper studies the direct pin pressing where metallic pins with undercutting geometries, protruding from the metal component, are inserted into a locally infrared heated CFRT component. The aim is to investigate the joining process with a focus on the filling of the undercut features with matrix and fibers to create a primarily form-fitting joint. For good mechanical properties of the joint, it is crucial, that the undercutting features are filled and do not lead to significant deconsolidations. The pin structures are manufactured from 42CrMo4 steel on a cnc-lathe and are joined via welding with HCT600+Zn sheet metal. The CFRT samples are manufactured from polypropylene and approximately 45% vol. unidirectional glass fibers. In the scope of this study, different pin geometries are joined with varying process settings and micro sections of the joints are investigated via reflected light microscopy. It could be shown that the undercuts can be completely filled with matrix and fiber material using the described process route. Based on the optical investigations a suitable setting of joining parameters is defined and lap shear as well as cross head samples are manufactured and experimentally tested. It could be seen that independently from the pin geometry the lap shear strength was primarily limited due to shear failure of the pin structures and it is assumed that the base diameter and pin strength predominantly determine the joint strength. Cross head samples failed due to pin extraction. Here, a significant increase of the joint strength with undercutting features could be shown in comparison to cylindrical reference pins.